The Far Horizons of Time. Time and Mind in the Universe - Ransford, H. Chris (De Gruyter, 2015)
What is Time? Assuming no prior specialized knowledge by the reader, the book raises specific, hitherto overlooked questions about how time works, such as how and why anyone can be made to be, at the very same instant, simultaneous with events that are actually days apart. It examines abiding issues in the physics of time or at its periphery which still elude a full explanation ? such as delayed choice experiments, the brain's perception of time during saccadic masking, and more ? and suggests that these phenomena can only exist because they ultimately obey applicable mathematics, thereby agreeing with a modern view that the universe and everything within it, including the mind, are ultimately mathematical structures. It delves into how a number of conundrums, such as the weak Anthropic Principle, could be resolved, and how such resolutions could be tested experimentally. All its various threads converge towards a same new vision of the ultimate essence of time, seen as a side effect from a deeper reality.